Turnbackhoax.id: Upaya Pemutusan Disinformasi Berita-berita Pemilu 2024 - Haqqo, Arinal; Ansoriyah, Siti (Program Studi Magister Linguistik Terapan UNJ, 2023)
The rise of disinformation in the midst of the development of new media is the impact of the lack of digital literacy of the community, especially active users of users. Ahead of the biggest political contestation in Indonesia, namely the 2024 election (Pemilu 2024), the government and society are again faced with the threat of hoaxes related to social, political and governance issues. The number of novice voters that will dominate is in fact related to the potential for more massive spread of hoaxes in cyberspace. The lack of digital literacy insights from first-time voters familiar with the internet and new media complicates efforts to disinfect and prevent disinformation. To anticipate the recurrence of the hoax phenomenon from the 2019 election, this study examines the mitigation of the spread of disinformation by identifying the types of content circulating and presenting evidence on the turnbackhoax.id portal initiated by the Indonesian anti-hoax movement. This descriptive qualitative research uses data from the turnbackhoax.id portal published during June 2023. The results explain how to make people more careful in reading information, verifying the truth of news and actively participating in providing accurate news sources and providing it in the portal in order for more internet users can verify the truth of the news.